Design and Simulation Analysis for Double Globoidal Cam-type ATC Device based on RecurDyn - Ge Zhenghao; Li Sen; Si Xianyong; Cao Peng (Jixie chuandong)
As the key component of machining center,the structure and driving mode of ATC device directly influence the time and efficiency of tool changing. Starting from the structure and principle of the cam-type ATC device,based on the theory of globoidal cam mechanism,the double globoidal cam linkage structure is designed to achieve the tool change action for ATC device. Taking the starting point of rotary globoidal cam indexing as the feature position and the motion cycle chart is designed to meet the k tool changing action. And then the digital mock- up of the double globoidal cam- type ATC device are obtained in Pro / Engineer. At last,the virtual prototype of the ATC device is built by using Recur Dyn with dynamic simulation and analysis,the real motion process of ATC device is simulated and the motion parameter curve is output,the results show that the accuracy of the design results are verified.